Effect of a probiotic preparation on the composition of the intestinal microbiome of rabbits - Skvortsova, E. G.; Filinskaya, O. V.; Bushkareva, A. S.; Bogdanova, A. A.; Mostofina, A. V.; Pivovarova, E. A. (Diponegoro University, 2025)
In this work, we studied the effect of a probiotic supplement containing bacteria of the Bacillus amyloliquefaciens strain (Vetom 2) on the intestinal microbiome composition of rabbits. Rabbits of the experimental group, in addition to compound feed together with water, received the Vetom 2.0 probi-otic feed additive in the amount of 50 mg / kg of live weight of 10 days every 30 days for four months. Genomic DNA was isolated from the intestines of rabbits using a set of ExtractDNABlood&Cells Am-plification of variable regions V3–V4 of the 16S rRNA gene using universal primers and subsequent sequencing on the IlluminaMiSeq platform. Bioinformatic analysis was carried out in the QIIME2 en-vironment. The control and experimental groups of crossbred rabbits were dominated by five phyla of intestinal bacteria: Bacillota, Pseudomonadota, Bacteroidota, Actinomycetota, and Verrucomicrobiota. The following taxa prevailed at the level of the orders: Eubacteriales, Pseudomonadales, Bacteroi-dales, Caryophanales, Enterobacteriales. At the family level, the most important taxa showing signifi-cant differences between the groups were Oscillospiraceae, Lachnospiraceae, and Campylobacterace-ae. The probiotic supplement contributed to an increase in the proportion of positive microorganisms, a decrease in the proportion of conditionally pathogenic, and an increase in the biological diversity of the intestinal microbiocenosis.